1995
DOI: 10.1002/gps.930100310
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression in the carers of dementia sufferers

Abstract: The survey aims to evaluate psychiatric morbidity in the carers of dementia sufferers using a semi-structured psychiatric interview. The case notes of consecutive referrals to four psychiatric services for the elderly in the West Midlands and a memory clinic service in Bristol were reviewed. All referrals who fulfilled the CAMDEX criteria for mild or moderate dementia and had a carer in contact at least once a week were contacted. Participants were assessed using a detailed package which included a Geriatric M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…High levels of caregiver psychological morbidity have been extensively documented (Brodaty and Hadzi-Pavlovic, 1990;Coope et al, 1995;Gallagher et al, 1989;Gilleard, 1984;Morris et al, 1988;Zarit et al, 1985). A model can be devised, based on that proposed by Poulshock and Deimling (1984), which is helpful heuristically and clinically to explain caregiver strain (Fig.…”
Section: Theoretical Underpinnings Of Intervention Programmesmentioning
confidence: 94%
“…High levels of caregiver psychological morbidity have been extensively documented (Brodaty and Hadzi-Pavlovic, 1990;Coope et al, 1995;Gallagher et al, 1989;Gilleard, 1984;Morris et al, 1988;Zarit et al, 1985). A model can be devised, based on that proposed by Poulshock and Deimling (1984), which is helpful heuristically and clinically to explain caregiver strain (Fig.…”
Section: Theoretical Underpinnings Of Intervention Programmesmentioning
confidence: 94%
“…In the three studies using RDC-criteria for depressive disorders (Coope et al, 1995;Gallagher et al, 1989;Lowery et al, 2000), a distinction was made between major, intermittent and minor depression. Major depression according to RDC-criteria is comparable to major depressive disorder according to DSM-III and DSM-III-R criteria.…”
Section: Prevalence Of Depressive Disordersmentioning
confidence: 99%
“…Anxietyencompassing feelings of worry and fear, and physical symptoms including muscular tension and somatic symptoms -has been relatively neglected in this group. The only previous systematic review to include the prevalence and correlates of anxiety in caregivers for people with dementia (CG) found only seven studies measuring anxiety (1989-1995Schulz et al, 1995). The authors reported that anxiety prevalence was significantly increased in CG compared with the general population.…”
Section: Introductionmentioning
confidence: 96%